Power Flow Control by Unified Power Flow Controller - Khan, M. Y. A.; Khalil, U.; Khan, H.; Uddin, A.; Ahmed, S. (Engineering, Technology & Applied Science Research, 2019)
The demand for electricity is increasing day by day and we have to produce more electrical energy to meet the load demands. Most of the experts prefer to extend the existing electrical networks over building the new network with greater costs. In this paper, the implementation of the flexible AC transmission systems (FACTS) devices in a simple electrical network is described. FACTS devices enhance power transfer capacity of the line without laying out new transmission line. These devices also protect the system from overloading in case of any contingency in the electrical network. Moreover, this paper describes the impacts of FACTS devices on improving the voltage stability and power handling capability of a transmission line. The proposed methods for the controllable flow of active and reactive power in a transmission line are also elaborated. A simple electrical system is examined to explain the improvement in the constraints of power system using FACTS devices.